2002
DOI: 10.1097/00005053-200211000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in Adolescent Girls With Anorexia: Relationship to Comorbid Psychopathology

Abstract: This study investigated the relationship between dissociation and psychological symptoms in adolescent girls with anorexia. First, the psychometric properties of the Adolescent Dissociative Experiences Scale (A-DES) were examined using data from 181 nonclinical adolescent boys and girls. Thereafter, A-DES scores and correlations with a range of psychological symptoms were compared across 20 girls with anorexia, 19 mixed clinical girls, and 86 nonclinical girls. The A-DES had a one-factor structure and good psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Several studies have demonstrated that higher levels of dissociation were associated with more severe symptoms of anorexia (Everill and Waller 1995;Vanderlinden et al 1993) and with noncompliance to treatment (Waller 1997). Moreover, Farrington et al (2002) showed that adolescent girls with anorexia appeared to use dissociation specifically to avoid processing angry affect with an interpersonal basis, similar to alexithymic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that higher levels of dissociation were associated with more severe symptoms of anorexia (Everill and Waller 1995;Vanderlinden et al 1993) and with noncompliance to treatment (Waller 1997). Moreover, Farrington et al (2002) showed that adolescent girls with anorexia appeared to use dissociation specifically to avoid processing angry affect with an interpersonal basis, similar to alexithymic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The A-DES was reported to have good reliability and validity (Armstrong et al, 1997;Smith & Carlson, 1996) and has been used frequently since its initial development to examine a variety of topics related to psychiatric problems in adolescents. For example, relationships between A-DES scores and experiences of past abuse by parents (Brunner, Parzer, Schuld, & Resch, 2000), symptomatology in anorexia nervosa (Farrington et al, 2002), self-mutilation (Matsumoto et al, 2005) et al, 2003), and hallucinatory experiences (Yoshizumi, Murase, Honjo, Kaneko, & Murakami, 2004) have been reported.…”
mentioning
confidence: 99%
“…The finding that the influence of non-interpersonal traumas had the largest influence on dissociation was unexpected. One interpretation could be that there might be a possible linkage to difficulties in affect regulation found in other eating disorder patients (36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…A particularly interesting group is patients with eating disorders since many studies have found that dissociative symptoms are more common in individuals with eating disorders (36)(37)(38). A substantial number of persons with eating disorders (20-50%) have been found to have both dissociative symptoms and a background of traumatic experiences (16,(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%